2010
DOI: 10.1073/pnas.1017547108
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-specific protein 1 identifies an inflammatory subpopulation of macrophages in the liver

Abstract: Cirrhosis is the end result of chronic liver disease. Hepatic stellate cells (HSC) are believed to be the major source of collagenproducing myofibroblasts in cirrhotic livers. Portal fibroblasts, bone marrow-derived cells, and epithelial to mesenchymal transition (EMT) might also contribute to the myofibroblast population in damaged livers. Fibroblast-specific protein 1 (FSP1, also called S100A4) is considered a marker of fibroblasts in different organs undergoing tissue remodeling and is used to identify fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
243
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(255 citation statements)
references
References 44 publications
10
243
1
1
Order By: Relevance
“…Together, in healthy ventricles, 95% of all GFP + fibroblasts were of endocardial or epicardial origin, and none of them were hematopoietically derived, as the Vav-Cre driver exclusively labeled CD45 + or PECAM1 + cells. After aortic bending, both epicardial-and endocardial-derived fibroblasts underwent transient proliferaOn the other hand, FSP1, which is frequently used as a cardiac fibroblast marker (10), was almost exclusively expressed in CD45 + cells, with no expression detected in interstitial GFP + fibroblasts and a limited presence in perivascular GFP + fibroblasts; therefore, similar to previous studies (11,12), FSP1 preferentially labeled immune cells. Hence, Moore-Morris et al have identified collagen1a1-GFP as a robust and specific marker of cardiac fibroblasts in both healthy and pressureoverloaded hearts.…”
supporting
confidence: 62%
“…Together, in healthy ventricles, 95% of all GFP + fibroblasts were of endocardial or epicardial origin, and none of them were hematopoietically derived, as the Vav-Cre driver exclusively labeled CD45 + or PECAM1 + cells. After aortic bending, both epicardial-and endocardial-derived fibroblasts underwent transient proliferaOn the other hand, FSP1, which is frequently used as a cardiac fibroblast marker (10), was almost exclusively expressed in CD45 + cells, with no expression detected in interstitial GFP + fibroblasts and a limited presence in perivascular GFP + fibroblasts; therefore, similar to previous studies (11,12), FSP1 preferentially labeled immune cells. Hence, Moore-Morris et al have identified collagen1a1-GFP as a robust and specific marker of cardiac fibroblasts in both healthy and pressureoverloaded hearts.…”
supporting
confidence: 62%
“…Recently, it was found that S100A4 + cells in liver were a subtype of macrophages. 23 However, it seems that S100A4 is expressed in different types of cells in various tissues. 45 , 46 The cellular origin of S100A4 in the colon is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…17 , 18 Previous studies have reported that S100A4 is expressed in a variety of cells, such as fibroblasts, macrophages, and malignant cells, and plays a crucial role in mediating tumor-stromal interplay. 19-23 S100A4 functions as both intracellular and extracellular forms. 24 , 25 Intracellular S100A4 is involved in a wide range of biological functions, such as the regulation of angiogenesis, cell survival, motility, invasion or metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The real involvement of EMT as a pathogenic mechanism contributing to liver fibrogenesis in CLDs is then more than controversial, with accumulating evidence deposing against EMT from either hepatocytes or cholangiocytes [31][32][33][34][35][36]. Along these lines, an excellent very recent fate tracing study from the laboratory of Robert Schwabe, performed using a novel Cre-transgenic mouse that marks 99% of hepatic stellate cells, has shown that HSCs give rise to 82-96% of myofibroblasts in models of toxic, cholestatic and fatty liver disease [37].…”
Section: Epithelial To Mesenchymal Transition (Emt) Process and Livermentioning
confidence: 99%